PERKEMBANGAN IMPLEMENTASI PASAR KARBON HUTAN DI INDONESIA - Deden Djaenudin; Mega Lugina; Ramawati Ramawati; Galih Kartikasari; Indartik Indartik; Mirna Aulia Pribadi; Satria Astana (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2016)
REDD+ carbon market can be an incentive for implementation ofREDD+ actors in the field. The facing problem is the high ofmarket uncertainty due to the unavailability ofcarbon transaction mechanism. The commitment oflocal government, relatively high as indicated by the formulation ofregulations that support the REDD+ implementation. Activity within REDD+ framework mainly is in order to maintain forest sustainability, revenue from carbon trading will be giving out additional benefit ifcarbon market occurred. Local government has not understood well on the carbon market procedure or its mechanism including carbon standard and methodology for producing carbon credit. Incentives for the achievement ofemissions reductions are more likely based on their roles in the sustainable forest management/improvement community's welfare instead of carbon credit. However, at the local level there are some voluntary forest carbon payment initiatives. The amount of proportionshouldconsidersharinginvestment costs, both between donors (buyers) and government. Registry agency need to be established in order to manage activities, oversee achievement of emission reduction, and facilitate the implementation of REDD+ in the field, and should have a task to set up a system ofincentives and disincentives in the management leakage risk and non-permanence.